2019
DOI: 10.1002/anie.201907349
|View full text |Cite
|
Sign up to set email alerts
|

Diversity‐Oriented Synthesis of α‐Functionalized Acylborons and Borylated Heteroarenes by Nucleophilic Ring Opening of α‐Chloroepoxyboronates

Abstract: The ring-opening reactions of N-methyliminodiacetyl (MIDA) a-chloroepoxyboronates with different nucleophiles allowt he modular synthesis of ad iverse arrayo f organoboronates.T hese include seven types of a-functionalized acylboronates and seven types of borylated heteroarenes, some of which are difficult-to-access products using alternative methods.T he common synthons, a-chloroepoxyboronates, could be viably synthesized by at wo-step procedure from the corresponding alkenyl MIDAb oronates.M ild reaction con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 95 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…In addition, the oxidation of the alkenyl boronates or α‐hydroxy alkylboronates to approach MIDA‐protected acylboronates or KATs has been developed by groups of Yudin, [8] Perrin, [9] Ito [10] and Sharma [11] . More recently, Wang reported the nucleophilic ring opening of α‐chloroepoxyboronates to synthesize α‐functionalized acylborons [12] . Although these methods provide diverse approaches for synthesis of acylborons, they often require multi‐step preparation of the precursors or use of stoichiometric reactive organometallic reagents and oxidants.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the oxidation of the alkenyl boronates or α‐hydroxy alkylboronates to approach MIDA‐protected acylboronates or KATs has been developed by groups of Yudin, [8] Perrin, [9] Ito [10] and Sharma [11] . More recently, Wang reported the nucleophilic ring opening of α‐chloroepoxyboronates to synthesize α‐functionalized acylborons [12] . Although these methods provide diverse approaches for synthesis of acylborons, they often require multi‐step preparation of the precursors or use of stoichiometric reactive organometallic reagents and oxidants.…”
Section: Methodsmentioning
confidence: 99%
“…MIDA boronates 60 also appeared to be suitable substrates for epoxidation; in this case, mCPBA was appropriate oxidant to achieve this transformation (Scheme 27). [61][62][63][64][65][66] The method was compatible with a wide range of substrates including mono-, di-, and trisubstituted derivatives with alkyl, aryl, SiMe 3 , Cl, and other substituents.…”
Section: Scheme 26 Epoxidation Of Potassium Vinyl Trifluoroborate 59 mentioning
confidence: 99%
“…[51] Recently,t he same group reported that ring opening of these a-chloroepoxyboronates towards the acylboron occurs upon treatment with nucleophiles without the requirement of aL ewis acid. [52] Using different nucleophiles (C,N ,O ,S , halides) to induce epoxide opening of 52,several a-functionalized acyl MIDAb oronates 53 were formed in moderate to excellent yields (Scheme 23). This greatly improves the access to as pectrum of secondary acyl MIDAb oronates.V inyl boronic esters are widely accessible,although the downside of this methodology is the low-yielding,d elicate epoxidation step.…”
Section: Angewandte Chemiementioning
confidence: 99%